Father- and Mother-Adolescent Decision-Making in Mexican-Origin Families - Perez-Brena, Norma (2011)
Understanding the prevalence and correlates of decisional autonomy within specific cultural contexts is necessary to fully understand how family processes are embedded within culture. The goals of this study were to describe mothers’ and fathers’ decision-making with adolescents (M = 12.51 years, SD = 0.58; 51% female), including parent-unilateral, joint, and youth-unilateral decision-making, and to examine the socio-cultural and family characteristics associated with these different types of decision-making in 246 Mexican-origin families. Mothers reported more joint and youth-unilateral decision-making and less parent-unilateral decision-making than did fathers. Fathers reported more youth-unilateral decision-making with sons than with daughters. Further, for mothers, more traditional gender role attitudes and higher levels of mother-adolescent conflict were associated with more parent-unilateral and less joint decision-making. In contrast, for fathers, lower levels of respect values were associated with more youth-unilateral decision-making with sons, and higher levels of parent-adolescent warmth was associated with more youth-unilateral decision-making with daughters. The importance of understanding the different correlates of mothers’ and fathers’ decision-making with sons versus daughters is discussed.